Trend and Causes of Overweight and Obesity among Pre-School Children in Kuwait - Nawal Alqaoud; Ayoub Al-Jawaldeh; Fahima Al-Anazi; Monica Subhakaran; Radhouene Doggui (MDPI AG, 2021)
Identifying life risk factors of obesity early will help inform policymakers to design evidence-based interventions. The following study aims to assess the trend of overweight and obesity over four years among pre-school Kuwait children, and to examine their association with breakfast skipping (BF), sugary and sweetened beverage (SSB) consumption, and screen time. Children aged 2-5 years (n = 5304) were selected from 2016 to 2019 national surveys. Overweight and obesity were defined according to the World Health Organization references. The children's mothers were asked about the BF of their children the day of the survey, their frequency of SSB consumption, and their weekly screen time use. Logistic regression was used to identify the risk factors associated with overweight/obesity. No significant decline (p values ≥ 0.12) was found for both overweight and obesity. Contrastingly, BF skipping, SSB consumption, and screen time declined (p < 0.0001). The BF skippers were found to have a 31% lower risk of being overweight. Daily TV watching, for 2-3 h, increases the odds of obesity by 5.6-fold. Our findings are encouraging regarding the decline in risky behaviours over time. However, more effort should be made both at the micro- and macro-level for a sustainable reduction in overweight and obesity.